2023
DOI: 10.1039/d2qo01908f
|View full text |Cite
|
Sign up to set email alerts
|

Bromine radical enhanced stoichiometric pyridylation of alkylarenes and diarylmethanes at room temperature

Abstract: A radical-radical coupling of readily available alkylarenes or diarylmethanes with cheap abundant 4-cyanopyridine is developed in stoichiometric manner and room temperature. This method employed broadly applicable petroleum-derived toluene derivatives as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Using LiBr as HAT reagent, Deng and coworkerd developed a photoredox‐catalyzed 4‐pyridination of readily available alkylarenes and diarylmethanes with cheap and abundant 4‐cyanopyridine in a stoichiometric manner (Scheme 18). [26] This method employs broadly applicable petroleum‐derived toluene derivatives as latent alkylating reagents, providing access to diarylmethanes and triarylmethanes in which at least one aryl is azaaryl. Mechanistic studies showed that the bromine radical was a selective hydrogen atom transfer (HAT) species that could quickly abstract hydrogen atoms from benzyl C−H bonds.…”
Section: Redox‐neutral Cross‐coupling Reactionsmentioning
confidence: 99%
“…Using LiBr as HAT reagent, Deng and coworkerd developed a photoredox‐catalyzed 4‐pyridination of readily available alkylarenes and diarylmethanes with cheap and abundant 4‐cyanopyridine in a stoichiometric manner (Scheme 18). [26] This method employs broadly applicable petroleum‐derived toluene derivatives as latent alkylating reagents, providing access to diarylmethanes and triarylmethanes in which at least one aryl is azaaryl. Mechanistic studies showed that the bromine radical was a selective hydrogen atom transfer (HAT) species that could quickly abstract hydrogen atoms from benzyl C−H bonds.…”
Section: Redox‐neutral Cross‐coupling Reactionsmentioning
confidence: 99%
“…The conversion of the 6-membered ring substrate to the 5- A novel library of highly functionalized phthalimides 67 was constructed by Deng and co-workers in 2023 (Scheme 45). 73 In this strategy, maleimides 44 and acetophenones 66 were used as starting materials and H 2 O acted as an oxygen source. By the H 2 O 18 isotope labelling experiment, the authors could prove that the oxygen of phenolic in the product originated from…”
Section: Metal-free Synthesis Of Phthalimidesmentioning
confidence: 99%
“…The synthesis of maleimide derivatives has been extensively investigated and remains a subject of considerable research interest in recent years [4] . However, the predominant approaches focused on the alteration of monocyclic rings (Scheme 1a), [4a–e] with limited documentation on the synthesis of bicyclic maleimide frameworks [4f–h] …”
Section: Introductionmentioning
confidence: 99%